Tolerance Education In Islamic Boarding School In Banten Province - Suhiroh, Iroh; Wahyuddin, Wawan; Muslihah, Eneng; Tarihoran, Naf’an; Wasehudin, Wasehudin (LPPM Universitas PGRI Sumatera Barat, 2025)
Study This aim For analyze implementation education tolerance in some cottage Islamic boarding schools in Banten Province. Focus main study This is How education tolerance taught in system learning, habituation, and culture daily life santri. Research This use approach qualitative with method descriptive. Data collected through observation, interviews, and documentation from four cottage selected Islamic boarding schools in Banten based on diversity background behind students and methods applied learning.Research result show that education tolerance in Islamic boarding schools implemented through three approach main : integration in curriculum, exemplary behavior of kyai and ustadz, as well as culture daily life students who reflect attitude each other honor. In the curriculum, values tolerance integrated through eye lesson like morals, Islamic history, and education citizenship. Kyai and ustadz become role model for students with show attitude moderate and open to diversity. In addition, culture Islamic boarding schools that emphasize deliberation, work the same, and mutual value between students become factor key in formation character tolerant.However, research this also found a number of challenge in implementation education tolerance, including limitations structure systematic curriculum, still existence view exclusive among students, as well as influence negative from environment outside and social media that can trigger attitude intolerance. For overcome challenge this research recommend strengthening material education tolerance in curriculum, training for power educator in apply approach inclusive, as well as improvement interaction students with a more diverse society diverse.Study This contribute in enrich understanding about education tolerance in context Islamic boarding school as well as give recommendation for manager Islamic boarding schools, government, and organizations social in effort create environment more education inclusive. With implementation of appropriate strategies, Islamic boarding schools can Keep going play a role as institution education that shapes generation tolerant, insightful students multicultural, and capable contribute in guard harmony social in Indonesia